Candida albicans Mrv8, is involved in epithelial damage and biofilm formation - Costa, Anna Carolina Borges Pereira [UNESP]; Back-Brito, Graziella Nuernberg [UNESP]; Mayer, François L.; Hube, Bernhard; Wilson, Duncan (Oxford University Press (OUP), 2020)
Candida albicans is the most common human fungal pathogen that can cause superficial and deep-seated infections in susceptible individuals. Despite its medical importance, the vast majority of C. albicans genes remain of unknown function. Here, we report a role for the lineage-specific gene, MRV8, in host pathogen interactions, mycelial microcolony maturation and biofilm formation. In silico analysis indicated that MRV8 encodes a four-pass transmembrane protein unique to the closely related pathogens C. albicans and Candida dubliniensis. Deletion of MRV8 did not affect C. albicans adherence to, or initial invasion into human oral epithelia, but inhibited mycelial development and strongly reduced epithelial damage. mrv8Δ/Δ cells exhibited a media-dependent defect in biofilm formation and mutant biofilm metabolic activity was enhanced by cyclosporin A. mrv8Δ/Δ biofilms were more tolerant to treatment with caspofungin, but not to fluconazole or amphotericin B. Co-stimulation with calcium chloride and calcofluor white rescued biofilm growth in the presence of caspofungin, and this rescue-effect was Mrv8-dependent. Together, our data demonstrate an important role for a lineage-specific gene (MRV8) in C. albicans biofilm formation, drug tolerance and host-pathogen interactions.
Keywords: Biofilm; Calcium homeostasis; Candida albicans; Caspofungin; Host-pathogen interaction; Marvel family